Topics associated with conflict in print news coverage of the HPV vaccine during 2005 to 2009 - Casciotti, Dana M (Hum Vaccin Immunother, 2015)
HPV vaccines represent a significant advancement for cancer prevention, but vaccination against a sexually transmitted infection and possible vaccine mandates have created considerable negative publicity. We sought to understand media portrayal of vaccine-related controversy, and potential influences on attitudes and vaccine acceptance. We analyzed characteristics of media coverage of the HPV vaccine in 13 US newspapers between June 2005-May 2009, as well as relationships between conflict and pro-vaccine tone and specific story characteristics. The four-year timeframe was selected to capture coverage during the development of the vaccine, the period immediately pre- and post-approval, and the time of widespread recommendation and initial uptake. This allowed the exploration of a range of issues and provided an understanding of how coverage changed over time. Analysis included 447 news stories and opinion pieces, the majority of which were published in 2007. Most articles were positive (pro-vaccine) in tone, prompted by research/scientific advancement or legislative activities. We deemed 66% of all stories conflict-containing. Fewer articles from 2005–2006 and 2008–2009 contained conflict than those from 2007, suggesting a peak period of concern, followed by gradual acceptance of the HPV vaccine. Legislative activities and content related to sexual activity were sources of conflict in HPV vaccine media messages. Health communication strategies can be improved by understanding and addressing potential sources of conflict in news coverage of public health initiatives.